Swami Vivekananda’s Introspection on Education: A Study based on 24 Parganas(s), West Bengal, India - Subhadeep Dutta (International Journal of Emerging Issues in Early Childhood Education, 2019)
Education is part and parcel of our life we cannot live without education so education is called the backbone-mirror of our society. Human-being is superior to other animals, animals can be trained but human-beings can be educated. Education is a dynamic process that starts from birth and continues until death. Education has two major parts first one is social education and the second one is formal education both are the dependent variable with each other. This project mainly deals with formal education, the study analysis of different aspects which will affect our education system in SOUTH 24 PARGANAS DISTRICT. The research design undertaken for the study was descriptive research and the convenience sampling method is used and the sample size consists of 200 respondents. Only a simple percentage analysis method used to analyze collected data and results of the study shows that education system has both positive-negative impacts on teachers, students and guardians' satisfaction.DOI: http://doi.org/10.31098/ijeiece.v1i2.35